2010
DOI: 10.1002/ijc.25361
|View full text |Cite
|
Sign up to set email alerts
|

The detection of circulating human papillomavirus‐specific T cells is associated with improved survival of patients with deeply infiltrating tumors

Abstract: A detailed analyses of HPV-specific immunity was performed in a large group of patients with HPV-induced cervical cancer (CxCa) in relation to HLA-types and prognostic factors. Patients were HLA-typed and HPV16/18-specific T-cell immunity was assessed by proliferation assay and cytometric bead array using freshly isolated PBMC and by phenotypic analysis of HPVspecific T cells. The results were analyzed in relation to known disease-related HLA-types (DR7, DR13, DR15/DQ06), invasiondepth and size of tumor, lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
(59 reference statements)
3
40
0
3
Order By: Relevance
“…Circulating T cells reacting against HPV16 E6 or E7 peptides were detected in the blood, often in patients with an HPV16þ tumor, largely extending previous data on HLA-A2 restricted T cells in a small group of patients 7 Similar to what was observed in patients with cervical carcinoma the HPV16-specific T-cell proliferative responses in HNSCC were not/hardly ever accompanied by the production of IFNc. 26,32 Although these responses in the blood clearly show that adaptive immune responses are induced upon exposure to the HPV viral oncoproteins, this reaction does not necessarily reflect an ongoing immune response against the tumor. This is exemplified by the detection of circulating HPV16-specific T cells in the blood of some patients with HPV-negative tumors, which in a number of cases displayed a similar cytokine profile as described for HPV16-specific reactivity in healthy females.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating T cells reacting against HPV16 E6 or E7 peptides were detected in the blood, often in patients with an HPV16þ tumor, largely extending previous data on HLA-A2 restricted T cells in a small group of patients 7 Similar to what was observed in patients with cervical carcinoma the HPV16-specific T-cell proliferative responses in HNSCC were not/hardly ever accompanied by the production of IFNc. 26,32 Although these responses in the blood clearly show that adaptive immune responses are induced upon exposure to the HPV viral oncoproteins, this reaction does not necessarily reflect an ongoing immune response against the tumor. This is exemplified by the detection of circulating HPV16-specific T cells in the blood of some patients with HPV-negative tumors, which in a number of cases displayed a similar cytokine profile as described for HPV16-specific reactivity in healthy females.…”
Section: Discussionmentioning
confidence: 99%
“…The most common high-risk types are the HPV-16 and HPV-18, respectively, associated with pre-cancers and cancers in various anogenital sites (e.g., cervix, vulva, vagina, and anus) (3)(4)(5)(6). The studies showed that HPV-specific T-cell responses induced by vaccines play an effective role in tumor regression (7)(8)(9)(10). The researchers indicated that therapeutic HPV vaccines have the potential to inhibit the tumor growth by targeting HPV oncoproteins (11).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has revealed that cervical extracts, in particular the protease component, can suppress lympho-proliferative responses [71], whereas expression of FasL on cervical tumors can cause apoptosis of the infiltrating lymphocytes [72]. These results also indicate that the production of regulatory T cells may be an important suppressive mechanism in cervical cancer [73,74], because regulatory T cells suppress the induction of type 1-helper T (Th1) cells [75], and IFN--producing Th cells are required to mobilize CD8 + T cells to the site of HPV infection [76]. Therefore, a successful immunotherapeutic approach to cervical cancer must circumvent the activity of these cells types and other local immunosuppressive mechanisms.…”
Section: Humoral Immune Responses and Cell-mediated Immune Responses mentioning
confidence: 99%